2010
DOI: 10.1002/adsc.201000159
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Limitations of Palladium‐Catalyzed Cross‐Coupling Reactions with Organogold Compounds

Abstract: Five different alkenylgold(I) phosphane complexes were prepared and then investigated in [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride-catalyzed cross-coupling reactions with different aryl halides, heterocyclic halides, an alkenyl halide, an alkynyl halide, allylic substrates, benzyl bromide and an acid chloride. With regard to the halides, the iodides were highly reactive, bromides or chlorides gave significantly reduced yields or failed, allylic acetates failed, too. The cross-coupling part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(54 citation statements)
references
References 64 publications
5
47
1
1
Order By: Relevance
“…However, more recently multiple studies have claimed otherwise and demonstrated the activity of gold nanoparticles in the reaction. For instance, PVP‐stabilised Au colloids in aqueous solution have been shown to be active and metallic Au nanoparticles supported on Al–Mg oxides have been shown to be active in a base‐free homocoupling reaction …”
Section: Resultsmentioning
confidence: 74%
“…However, more recently multiple studies have claimed otherwise and demonstrated the activity of gold nanoparticles in the reaction. For instance, PVP‐stabilised Au colloids in aqueous solution have been shown to be active and metallic Au nanoparticles supported on Al–Mg oxides have been shown to be active in a base‐free homocoupling reaction …”
Section: Resultsmentioning
confidence: 74%
“…[76][77][78] In this case, the gold serves as a transmetallation agent, and the use of a pre-formed Au I complex permits the transfer of the alkynyl or diynediyl species to Pd II under mild conditions. [79] In this manner, differentially substituted 1,3-diynes can be prepared by the sequential cross-coupling of each Au-alkynyl moiety in Ph 3 PAuCϵCCϵCAuPPh 3 (Scheme 4); similar Au-mediated transmetallation chemistry has been used in conjunction with Pd/Cu cycles in the synthesis of metal complexes featuring polyyn(di)yl ligands of considerable length.…”
Section: Metal-localised Redox Chemistrymentioning
confidence: 99%
“…Reports of at least partial success in interfacing Au- and Pd catalysis in this manner have been published by Blum, 10 Hashmi, 11 Sarkar, 12 and Sestelo. 13 In particular, Blum has reported an impressive example of bimetallic catalysis wherein a gold-vinyl intermediate obtained from an allene activation reaction could be intercepted by an in situ formed palladium π-allyl species to perform a vinyl-allyl coupling that was catalytic in both gold and palladium.…”
mentioning
confidence: 99%